Stable soliton dual-microcomb generation via sideband thermal compensation for spectroscopy - Miao, Runlin; Yin, Ke; Zhang, Chenxi; Yu, Zhuopei; Cheng, Xiang’ai; Jiang, Tian (Frontiers in Physics, 2022)
Microcombs—generated by coherently pumping nonlinear microresonators—have emerged as a state-of-the-art scheme at the chip scale. Dual-comb spectroscopy (DCS) technology further takes advantage of the miniature system, and has been demonstrated as a powerful tool for real-time and broadband optical sampling of molecular spectra. Here, a novel soliton dual-microcomb generation method by rapid frequency sweep and sideband thermal compensation is put forward, and dual-microcomb optical spectra range beyond 200-nm has been successfully demonstrated in two microresonators with moderate quality factors. Compared to the dual-microcomb with a weak thermal compensation effect, the demonstrated dual-microcomb shows much lower-noise RF beat notes (<10 kHz) and smaller Allan deviations (1.0×10−4 @ 1 ms) by increasing sideband power. Moreover, the dual-microcomb has been utilized in the gas absorption detection of H12CN for demonstration with high signal-to-noise ratios (SNRs) and fast acquisition rates. This work also lays a technical foundation for other dual-microcomb applications of ranging and microwave photonics.